Comparative investigation of multi-walled carbon nanotube modified diesel fuel and biogas in dual fuel mode on combustion, performance, and emission characteristics. (1st April 2022) - Atelge, M.R.; Arslan, Esenay; Krisa, David; Al-Samaraae, R.R.; Abut, Serdar; Ünalan, Sebahattin; Atabani, A.E.; Kahraman, Nafiz; Akansu, Selahaddin Orhan; Kaya, Mustafa; Sarıkoç, Selçuk; Demir Kıvrak, Hilal
Graphical abstract: Highlights: The highest Pmax was obtained from F2@60ppm at 100% load. The COVIMEP was improved with nano additive for all loads under dual fuel mode. BTEs of modified fuels under dual fuel mode were higher than F2 for all loads. The highest energy share was computed as 13.7% for F2 @60ppm at the full load. The drawback of modified fuels was observed NO emission under dual fuel mode. Abstract: Biogas has been investigated as an alternative biofuel in dual fuel operating mode in a direct injection diesel engine. However, there is not sufficient information about using modified fuels with biogas. This study aimed to investigate the effects of modified diesel fuel and biogas on combustion behavior, performance, and emissions characteristics at 1500 rpm constant speed with 5 different load conditions at an interval of 25%. Diesel was modified with multi-walled carbon nanotubes with 30, 60, and 90 ppm. Diesel fuel and three modified fuels were used as pilot fuel and biogas was introduced through the intake manifold with the flow rate of 500 g/h as the primary fuel. Diesel mode fuels were denominated F1 while dual fuel mode fuels were labeled as F2, and the concentration levels were given subscript such as F2 @60ppm . The experimental study revealed that modified fuel showed better combustion behaviors, performance, and emissions in comparison to diesel fuel. Further, the same trend was observed in the dual fuel mode. The maximum pressure of F2 @60 ppm was 1% higher than F2 under dual fuel mode at the full load. Moreover, the coefficient of variation of the indicated mean effective pressure for dual fuel mode was found approximately 9.2, 6.9, 6.2, and 7.2% for F2, F2 @30 ppm, F2 @60 ppm, and F2 @90 ppm, respectively at full load. In addition, the energy share of biogas increased by 7.9, 8.7, and 7.1% for F2 @30 ppm, F2 @60 ppm, and F2 @90 ppm, respectively in comparison with F2 at full load. The highest decrease of brake specific energy consumption under the dual mode was obtained to be an 8% drop from F2 @60 ppm compared to F2 at full load. At the same load, the brake thermal efficiency of F2 @30 ppm, F2 @60 ppm, and F2 @90 ppm were noted to be 30.2, 30.4, and 30.0%, respectively which are higher than F2 (27.9%). The value of replaced diesel with biogas was noted 0.09, 0.23, 0.24, and 0.22 kg/h for F2, F2 @30 ppm, F2 @60 ppm, and F2 @90 ppm, respectively under the full load condition. Lastly, CO and HC emissions were almost the same value with and without modified fuel for dual fuel mode at the full load. Nevertheless, NO emission was slightly increased with modified fuel compared to F2. From these findings, it can be suggested that 60 ppm multi-walled carbon nanotubes additive can be an optimum level for combustion, performance, and emissions under the dual fuel mode.